Analisis Pelaksanaan dan Dampak Program Indonesia Pintar (Pip) Di Sekolah Menengah Atas - Nabila, Nabila; Mauwa, Netda Konstantia; Young, Ji Suk; Ismanto, Bambang; Trisatyawati, Sophia (LPPM Institut Pendidikan Nusantara Global, 2025)
The Indonesia Smart Program (PIP) is an aid from the Indonesian government that aims to provide educational assistance to underprivileged students in order to increase access to education for all citizens. Given the importance of PIP funds in equalizing access to education, this program has challenges in its implementation that can affect the effectiveness of the PIP program. Therefore, this study aims to analyze the implementation of PIP in senior high schools to find the problems faced. This research uses a Mix Methods approach by giving questionnaires to students and in-depth interviews to school principals and parents. Data collection techniques use questionnaires, interviews and documentation. Qualitative data validation techniques use data triangulation and method triangulation. Quantitative data validation techniques use expert judgment. Qualitative data analysis uses Milles and Huberman techniques, which include data collection, data reduction, and drawing conclusions. Quantitative data analysis uses percentage analysis. The role of schools in the PIP program is to provide opportunities for students who experience economic constraints to obtain PIP assistance. Parents play a role in ensuring that the PIP funds obtained are budgeted for the fulfillment of children's educational needs and not for other purposes. So that the role of schools in monitoring students who receive PIP needs to be done systematically. The data obtained shows that PIP funds have a positive impact on meeting educational needs by 76.5% in the good category, the impact of PIP on academic aspects by 62.9% in the good category. The PIP program has an impact on motivation and sustainability of education by 72.94% in the good category.